The Enrichment of Learning English Model Based on Drama at Mardisiwi Islamic Kindergarten in Gendroprasto Surakarta, Indonesia - Slamet, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
In Indonesia, it is common for kindergartens to include English in their curriculums. Most teachers and parents assume that the children will absorb any information easily, including English as a foreign language. Mardisiwi Islamic Kindergarten (MIK) in Surakarta is one of kindergarten which encloses English into its curriculum. The study was qualitative researchusing Research and Development method. The source of the data derived from the interviews with the headmaster, teachers, and the students of MIK. In addition, class observation and documentation were conducted. The data was analyzed by collecting, reducing, presenting, and determining the conclusion. In fact, several problems arise dealing with the teacher’s expertise, method, and learning material. This study was aimed to identify the learning models, classify the strength and the weaknesses of the models, and to propound a teaching model to be implementedin Mardisiwi Islamic Kindergarten. The model covers the learning process, time allotment, media, and method. It also involves drama-based learning method.